Heart to heart : a conversation on love and hope for our precious planet - Bstan-ʼdzin-rgya-mtsho, Dalai Lama XIV, 1935- (Harper One, an imprint of HarperCollinsPublishers, 2023)
The spiritual leader of Tibetan Buddhists and the cartoonist and award-winning author of MUTTS join forces to call for a Compassionate Revolution that encourages everyone to work together to heal our relationships with each other and with the planet.